2020
DOI: 10.15252/embj.2020104708
|View full text |Cite
|
Sign up to set email alerts
|

The tRNA pseudouridine synthase TruB1 regulates the maturation of let‐7 miRNA

Abstract: Let-7 is an evolutionary conserved microRNA that mediates post-transcriptional gene silencing to regulate a wide range of biological processes, including development, differentiation, and tumor suppression. Let-7 biogenesis is tightly regulated by several RNA-binding proteins, including Lin28A/B, which represses let-7 maturation. To identify new regulators of let-7, we devised a cellbased functional screen of RNA-binding proteins using a let-7 sensor luciferase reporter and identified the tRNA pseudouridine sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 93 publications
(122 reference statements)
0
18
0
Order By: Relevance
“…METTL16 and NSUN2 both target similar types of ncRNAs, such as vault RNAs, Y RNAs, U6 snRNA and lncRNAs ( 44 , 58 , 59 ). HITS-CLIP analysis of TRUB1 revealed binding to several classes of ncRNAs, but the extent of overlap with METTL16 RNA targets remained unknown as the analysis focused mainly on pri-miRNAs and tRNAs ( 60 ). Future studies will address whether the potential interactions between these different modifiers detected by BioID result from their activity on the same RNA molecule or whether they localize to specific nuclear foci that are formed to facilitate RNA processing.…”
Section: Resultsmentioning
confidence: 99%
“…METTL16 and NSUN2 both target similar types of ncRNAs, such as vault RNAs, Y RNAs, U6 snRNA and lncRNAs ( 44 , 58 , 59 ). HITS-CLIP analysis of TRUB1 revealed binding to several classes of ncRNAs, but the extent of overlap with METTL16 RNA targets remained unknown as the analysis focused mainly on pri-miRNAs and tRNAs ( 60 ). Future studies will address whether the potential interactions between these different modifiers detected by BioID result from their activity on the same RNA molecule or whether they localize to specific nuclear foci that are formed to facilitate RNA processing.…”
Section: Resultsmentioning
confidence: 99%
“…The STRING analysis here reveals that PPRC1 interacts with TRUB1 (Figure 2), a synthase that catalyzes the pseudouridylation of mRNAs [126]. In 2020, Kurimoto et al [127] described the essential role of TRUB1 in the maturation of the miRNA let-7, an evolutionary conserved microRNA that mediates a post-transcriptional gene silencing regulating a wide range of biological processes, including development and differentiation [127]. The authors proposed that TRUB1 acts as a suppressor of cell proliferation, and therefore as a tumor suppressor, which is mediated in part by let-7 [127].…”
Section: Candidate Markers and Associated Functional Partnersmentioning
confidence: 79%
“…In 2020, Kurimoto et al [127] described the essential role of TRUB1 in the maturation of the miRNA let-7, an evolutionary conserved microRNA that mediates a post-transcriptional gene silencing regulating a wide range of biological processes, including development and differentiation [127]. The authors proposed that TRUB1 acts as a suppressor of cell proliferation, and therefore as a tumor suppressor, which is mediated in part by let-7 [127]. The STRING analysis also revealed that PPRC1 interacts with NOP56 and DKC1.…”
Section: Candidate Markers and Associated Functional Partnersmentioning
confidence: 99%
“…The pseudouridylation of different human RNA species is mediated by different pseudouridine synthases, such as pseudouridine synthase (PUS) 1, TruB pseudouridine synthase 2 (TRUB2), TRUB1, PUS3, PUS4, RNA pseudouridine synthase D3 (RPUSD3), RPUSD4, PUS7, pseudouridine synthase 7 like (PUS7L), PUS10 and DKC1 [ 28 ]. From these candidates, TRUB1 has been recently reported to modulate the stability of hsa-let-7 [ 51 ]. However, it is noteworthy that the actual list of enzymes involved in 2′-O-methylation and pseudouridylation of miRs might be incomplete.…”
Section: Resultsmentioning
confidence: 99%